Incentives to Identify: Errata - Antman, Francisca; Duncan, Brian (The Review of Economics and Statistics, 2019)
IN an article published in this review (Antman & Duncan, 2015), we document how racial identity responds to state affirmative action policy. A coding error was recently brought to our attention that resulted in 0.55% of our sample being misclassified in terms of their African ancestry.1 We regret and apologize for this error. Although the error affected only a tiny percent of the overall sample, the correction changes the conclusion of how individuals with multiracial African ancestry respond to state affirmative action bans, from a negative and statistically significant effect to a positive and statistically significant effect. The corrected table 3 shows the updated results. The coefficients for college-aged individuals with African ancestry reported in table 5 are also now positive, but are no longer statistically significant at conventional levels. Correcting the error does not change the conclusions for individuals with only African ancestry or no African ancestry. None of the Asian ancestry classifications, and thus none of the results for individuals with Asian ancestry (table 4 and the last two columns of table 5), were affected by the coding error. There are no meaningful changes to the summary statistics in table 2 except in the column for those with multiracial black ancestry. The most notable change is the fraction of individuals with multiracial black ancestry who self-identify as black: 49.37% in the original table and 90.86% in the updated table.2 (For further explanation and a complete set of updated results, see Antman & Duncan, 2019.) We continue to find that racial identity responds to state affirmative action policy, albeit with a different conclusion for multiracial blacks, and we are now able to distinguish stronger effects for multiracial individuals with more distant connections to their minority group.This is the original abstract: We link data on racial self-identification with changes in state-level affirmative action policies to ask whether racial self-identification responds to economic incentives. We find that after a state bans affirmative action, multiracial individuals who face an incentive to identify under affirmative action are about 30% less likely to identify with their minority group. In contrast, multiracial individuals who face a disincentive to identify under affirmative action are roughly 20% more likely to identify with their minority group once affirmative action policies are banned.We modify this original abstract as follows: We link data on racial self-identification with changes in state-level affirmative action policies to ask whether racial self-identification responds to economic incentives. We find that after a state bans affirmative action, multiracial individuals who face an incentive to identify under affirmative action are about 2% to 5% more likely to identify with their minority group. In contrast, multiracial individuals who face a disincentive to identify under affirmative action are roughly 20% more likely to identify with their minority group once affirmative action policies are banned.